P315 Molecular screening for Lynch syndrome in IBD colorectal cancer. (16th January 2018) - Anele, C; Worley, G; Georgiou, D; Moorghen, M; Faiz, O; Latchford, A
Abstract: Background: Inflammatory bowel disease (IBD) is a risk factor for colorectal cancer (CRC). Many IBD patients due to their young age at CRC diagnosis will fulfil Bethesda criteria for testing for Lynch syndrome (LS) (Box 1). Mismatch repair (MMR) immunohistochemistry (IHC) is often not performed due to the assumption that the CRC is entirely IBD-related. Lynch syndrome accounts for 3–5% of all CRC and it is caused by a mutation in one of the four MMR genes ( MLH1, PMS2, MSH2 and MSH6 ). The co-existence of IBD and LS is not well described in the literature. Identifying LS is important, not only for the patient's oncological management and surveillance but also risk stratification of their first degree relatives. We aim to assess the existence of MMR deficiency in IBD CRC. Methods: Patients diagnosed with IBD CRC under the age of 50 years were identified from our institution retrospective CRC database. The study period was between 2004 and 2016. Their clinicopathological characteristics, MMR IHC, and genetic results were retrieved from their medical and histopathology records. Results: Fifty-two patients with IBD CRC under the age of 50 were identified. Thirty-eight (73%) were male. The mean age at CRC diagnosis was 39.6 ± 1.2 years. Six (12%) patients had Crohn's disease and 46 (88%) had ulcerative colitis. Fourteen (29%) patients had CRC in the ascending colon, four (8%) in the transverse, four (8%) in descending colon, seven (14%) in sigmoid and 20 (41%) in rectum (Figure 1). Three (4%) patients had synchronous CRC. Twelve (23%) patients had MMR IHC performed on the resected tumour. Three (25%) were found to have loss of MMR protein of which one had loss of MLH1 and PMS2 and two had loss of MHS2 and MSH6. Of these, two were lost to follow-up without further genetic testing. One patient with MHS2 and MSH6 loss, only had germline test for MSH6 test performed which was normal. Conclusions: Our data show that MMR IHC testing is rarely performed on IBD CRC cases. When performed, loss of expression of one or more MMR protein is observed in 25%. With the introduction of universal molecular screening in England, local pathways to institute molecular screening and further investigation for and understanding the implications of mismatch repair loss are required.